THE STUDY ОF VАLUE-АDDED TАX: KNОWLEDGE FRОM THE EU VАT EXPERIENСE АND UZBEKISTAN'S VАT SYSTEM - Po’latov Sherzodbek Oybek о'g'li,; Musаbekоv Sherаli Nаzаrаli о’g’li, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The complex structure of the Value Added Tax (VAT) system in the European Union is captured in the abstract. It describes important elements including taxable transactions, standard rates, and the credit-invoice method. The historical shift from fiscal borders to administrative restrictions is discussed, highlighting the need to strike a careful balance between a consumption tax based on destination and a single internal market. In business-to-business transactions, mechanisms like the reverse charge technique and standardized identifying numbers are implemented. The abstract makes mention of several new difficulties that may arise, such as the complexity of place-of-taxation laws and the possibility of false refund claims. All in all, it gives a clear synopsis of the complex EU VAT system, including information on its composition and changing dynamics.